1993
DOI: 10.1159/000118984
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of Coffee on Alertness and Performance during the Day and Night

Abstract: An experiment was carried out to examine the effects of coffee on performance and alertness in the day and at night. The results showed that caffeinated coffee had a beneficial effect on alertness and improved performance on a variety of tasks in both day and night sessions. The effects were often very large. For example, at night, consumption of caffeinated coffee produced comparable alertness ratings to the day-time ratings given when juice was drunk. In contrast to the effects of caffeinated coffee, the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 5 publications
3
62
0
Order By: Relevance
“…Jarvis (1993) found significant improvements in simple reaction time, choice reaction time, incidental verbal memory and Visio-spatial reasoning after the intake of coffee. Similarly, Smith et al (1993) found significant effects of intake of coffee on alertness and performance. Various studies also targeted the use of a computer in mood regulation and the improvement of performance.…”
Section: Moods and Emotionsmentioning
confidence: 83%
“…Jarvis (1993) found significant improvements in simple reaction time, choice reaction time, incidental verbal memory and Visio-spatial reasoning after the intake of coffee. Similarly, Smith et al (1993) found significant effects of intake of coffee on alertness and performance. Various studies also targeted the use of a computer in mood regulation and the improvement of performance.…”
Section: Moods and Emotionsmentioning
confidence: 83%
“…Caffeine was found to either (1) exert no effects on free recall performance in sixteen studies [7][8][9]11,[21][22][23][24][25][26][27][28][29][30][31][32]; (2) improve recall in six studies [33][34][35][36][37][38]; or (3) impair recall in three studies [8,12,39].…”
Section: Short Term Memorymentioning
confidence: 99%
“…Convergent studies have shown the positive effects of caffeine on alertness and performance during daytime as well as during night time [46][47][48][49] . These effects can be felt as soon as a moderate amount of caffeine (between 2 and 4 mg/kg) is taken, whatever its shape (coffee, tea or energy drink) 50) .…”
Section: Intake Of Natural or Pharmacological Substancesmentioning
confidence: 99%